2013
DOI: 10.1074/mcp.m112.020701
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Analysis in Metastatic Renal Cell Carcinoma Reveals a Unique Set of Proteins with Potential Prognostic Significance

Abstract: Metastatic renal cell carcinoma (RCC) is one of the most treatment-resistant malignancies, and patients have a dismal prognosis, with a <10% five-year survival rate. The identification of markers that can predict the potential for metastases will have a great effect in improving patient outcomes. In this study, we used differential proteomics with isobaric tags for relative and absolute quantitation (iTRAQ) labeling and LC-MS/MS analysis to identify proteins that are differentially expressed in metastatic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 97 publications
6
79
0
Order By: Relevance
“…28 These observations imply that endogenous Gal-1 may play an important role in RCC progression. Although it has been reported that metastatic RCC tissues with poor prognosis show higher Gal-1 expression, 18 the molecular mechanisms of Gal-1 in progression of RCC still remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 These observations imply that endogenous Gal-1 may play an important role in RCC progression. Although it has been reported that metastatic RCC tissues with poor prognosis show higher Gal-1 expression, 18 the molecular mechanisms of Gal-1 in progression of RCC still remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Previous studies have suggested that Gal-1 may serve as a potential marker for RCC. 17,18 However, the detailed molecular mechanisms connecting Gal-1 to RCC remain largely unknown. The present study examined whether Gal-1 contributed to functional implications and clinical relevance in kidney cancer pathogenesis.…”
mentioning
confidence: 99%
“…Dysregulated protein expression in Cyld knockout kidney samples was verified by Western blot analysis as described before (Masui et al, 2013). The proteins used (and their antibodies) were: Hsd17b4 (Abcam ab170910) and AKR1B3 (ABcam ab175394).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…ITRAQ label technology together with nano liquid chromatography-mass spectrometry (NanoLC-MS/MS) has proven to be efficient in protein analysis (13)(14)(15). Hence, the clinic-combined metastatic model and this technological means will increase the likeliness of discovering new metastasis-associated genes (16) and proteins (17) for identifying new antitumor targets.…”
Section: Introductionmentioning
confidence: 99%